PROSES BERPIKIR REFRAKTIF MAHASISWA BERGAYA KOGNITIF INTUITIVE DALAM MENYELESAIKAN MASALAH KOMPLEKS - Kriswandani Kriswandani; Dani Kusuma (Jurnal Karya Pendidikan Matematika, 2022)
This study aims to describe and examine the refractive thinking process of students with intuitive cognitive styles in solving complex problems. This research is an exploratory, descriptive study with a qualitative approach. The prospective research subjects were SWCU and UMS Mathematics Education undergraduate students, totaling 239 students consisting of 155 SWCU students and 84 UMS students. The subjects of this study consisted of 2 students with intuitive cognitive styles. The research instruments include the main and supporting instruments, including complex problems, cognitive style questionnaires, and interview grids. This research results from the refractive thinking process of Mathematics Education students with an intuitive cognitive style in solving complex problems, including perplexity, investigation, construct, evaluation and decision. The stages of an investigation, construct, and evaluation is carried out repeatedly and not sequentially (randomly). The perplexity stage occurs not only at the beginning of the stage but also occurs at each stage of refractive thinking. In addition, students decide to make sewing scheduling guesses based on their intuition.